Tawasul Surah Al-Fatihah: Studi Perbandingan Nahdlatul Ulama dan Salafi - Saryadi Saryadi; Zakaria Husin Lubis; Badru Tamam (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines the differences and similarities between Nahdlatul Ulama and Salafi perspectives on the concept of tawasul through Surah Al-Fatihah and analyzes their socio-theological implications. Using a qualitative approach with library research and content analysis, the study explores religious texts and scholarly literature related to the issue. The findings reveal that the primary difference lies in the methodological approach to religious evidence and worship. Nahdlatul Ulama adopts a contextual ijtihad approach based on maqāṣid al-sharī‘ah and classical scholarly traditions, allowing beneficial religious practices that do not contradict Islamic teachings. In contrast, Salafi adheres to a tawqīfī approach, accepting only acts of worship explicitly supported by the Qur'an and authentic Sunnah while rejecting religious innovations. Consequently, Nahdlatul Ulama permits the recitation of Surah Al-Fatihah as a means of tawasul, including for the deceased, whereas Salafi rejects its ritual use due to the absence of specific textual evidence. Despite these differences, both groups uphold the principle of tawhid, affirm that prayers should be directed solely to Allah, accept tawasul through righteous deeds, recognize the virtues of Surah Al-Fatihah, and reject practices considered contrary to Islamic teachings.